Oxygen diffusion and consumption in extracellular matrix gels: Implications for designing three‐dimensional cultures. Issue 8 (30th September 2013) - Colom, Adai; Galgoczy, Roland; Almendros, Isaac; Xaubet, Antonio; Farré, Ramon; Alcaraz, Jordi
ABSTRACT Three‐dimensional (3D) cultures are increasingly used as tissue surrogates to study many physiopathological processes. However, to what extent current 3D culture protocols provide physiologic oxygen tension conditions remains ill defined. To address this limitation, oxygen tension was measured in a panel of acellular or cellularized extracellular matrix (ECM) gels with A549 cells, and analyzed in terms of oxygen diffusion and consumption. Gels included reconstituted basement membrane, fibrin and collagen. Oxygen diffusivity in acellular gels was up to 40% smaller than that of water, and the lower values were observed in the denser gels. In 3D cultures, physiologic oxygen tension was achieved after 2 days in dense (≥3 mg/mL) but not sparse gels, revealing that the latter gels are not suitable tissue surrogates in terms of oxygen distribution. In dense gels, we observed a dominant effect of ECM composition over density in oxygen consumption. All diffusion and consumption data were used in a simple model to estimate ranges for gel thickness, seeding density and time‐window that may support physiologic oxygen tension. Thus, we identified critical variables for oxygen tension in ECM gels, and introduced a model to assess initial values of these variables, which may short‐cut the optimization step of 3D culture studies. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 102A: 2776–2784, 2014.